Benzo[g]indole based Schiff's base ligand and its transition metal complexes: Synthesis, characterization and anti-microbial activity studies. (2022) - Rahaman, Fazlur; Gupta, Priti; Manjunatha, M.N.; Gautam, Prabhat
Abstract: A series of six new M (II) metal complexes where M = Cu, Co, Ni, Zn, Cd and Mn are derived from the Schiff base ( E )- N '-(1-(2-hydroxy-5-methylphenyl)ethylidene)-3-phenyl-1H-benzo[ g ]indole-2-carbohydrazide (HL). HL (1) was obtained by condensation of 3-phenyl-1H-benzo[g]indole-2-carbohydrazide (2) and 2-hydroxy-5-methylacetophenone (3) . HL (1) and its metal complexes were subsequently characterized using various analytical techniques such as elemental analysis, molar conductance measurements, magnetic susceptibility measurements, UV–Visible, FT-IR, 1 HNMR, FAB-mass, ESR, XRD and TGA spectral studies. Based on spectral studies, it was concluded that the Co(II), Ni(II) and Mn(II) complexes are octahedral in nature, Zn(II) & Cd(II) complexes possess tetrahedral geometry, while Cu (II) complex have square pyramidal geometry. The HL (1) and its complexes were tested for their antibacterial and antifungal activity by zone inhibition test method. The activity of metal complexes was found to be better than their Schiff base ligand HL (1) .